Brazilian Primary Health Care strategies during the COVID-19 pandemic: A scoping review - Bortoli, Maritsa Carla; Sanine, Patricia Rodrigues [UNESP]; de Araújo, Bruna Carolina; Oliveira, Cintia de Freitas; Costa, Maria Izabel Sanches; Tesser, Taís Rodrigues (FapUNIFESP (SciELO), 2023)
Primary Health Care is the gateway for users to access the Brazilian healthcare system and has been particularly affected by the COVID-19 pandemic demands. This review systematically identified and mapped evidence regarding novel or adapted strategies developed within PHC during the COVID-19 pandemic in Brazil. Our results are presented as a narrative synthesis following the JBI methodology. They were analyzed and discussed through the lens of the Health Work Process Theory, which al-lowed us to categorize the publications into two principal domains of strategies, managerial and clinical, encompassing strategies that were new, adapted, or maintained in healthcare services. Two hundred twenty-six interventions were identified (130 managerial and 96 clinical) from 49 studies. The new strategies appeared more fre-quently in both domains, while the maintained ones were less prevalent. The array of interventions highlights different care models, sometimes aligned with a biomedical approach. In contrast, others focus on comprehensiveness and longitu-dinality based on a person-centered care, in the family, and the community. Thus, this review identified that the same pre-pandemic challenges persist.
Estratégias dos serviços de Atenção Primária durante a pandemia da COVID-19 no Brasil: uma revisão de escopo
Keywords: Brazil; COVID-19; Primary Health Care; Scoping review. Health Services